Effect of copper content on the tensile elongation of Al–Cu–Mn–Zr alloys: Experiments and finite element simulations - Bahl, Sumit; Hu, Xiaohua; Hoar, Eric; Cheng, Jiahao; Haynes, J. Allen; Shyam, Amit (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2020)
Microstructures of cast aluminum alloys used in automotive engine applications often consist of intermetallic particles that can impact the tensile elongation of these alloys. Here, we investigate the effect of intermetallic grain boundary particles on tensile elongation by fabricating a series of alloys with Cu content varying between 6.0 - 9.0 wt% in cast Al–Cu–Mn–Zr (ACMZ) type compositions. The tensile elongation of as-aged ACMZ alloys decreases monotonically with increase in Cu content. While the microstructure within the grains and yield stress of the alloy remains invariant with Cu content, the decrease in tensile elongation correlates well with increase in the size and volume fraction of grain boundary particles. Microstructural observations are combined with finite element simulations to explain the trend in tensile elongation with changing Cu content. Crack initiation is found to occur by brittle fracture of the grain boundary particles. Increase in particle size promotes crack initiation by reduction in size dependent particle fracture strength. Lower inter-particle spacing at higher particle volume fraction further facilitates crack initiation by increasing stress within the particles caused by the interaction between stress fields of neighboring particles. Increase in particle volume fraction also accelerates crack propagation through the formation of macro shear zones in the microstructure. The increase in Cu content of cast ACMZ alloys, therefore, decreases tensile elongation by promoting both crack initiation and crack propagation.